Pengaruh Beban Kerja dan Kondisi Lingkungan Kerja Terhadap Kinerja Tenaga Medis di RS Syafira Pekanbaru - Desvi Emti; Rani Silvi Adilla (Al-Manar Journal of Economic and Social Studies, 2024)
This research was conducted at Syafira Hospital Pekanbaru. The purpose of this study was to determine the effect of workload and work environment on the performance of medical personnel at Syafira Hospital Pekanbaru, both partially and simultaneously. This study used purposive sampling technique with a sample of 73 respondents. The results showed that there was a positive and significant influence between workload on performance, the work environment had a positive and significant effect on performance. Simultaneously, workload and work environment have a significant effect on performance. From the determination test, it is known that the R Square value shows that workload and work environment together have an influence of 71% on the performance of medical personnel, and the remaining 29% is influenced by other variables not observed in this study.